Analysis of the gas exchange and water balance in a closed experimental model of the artificial ecosystem intended for an estimated portion of a human. (November 2018) - Ushakova, Sofya; Tikhomirova, Natalia; Velichko, Vladimir; Trifonov, Sergey; Morozov, Yegor; Kalacheva, Galina; Pavlova, Anastasia; Tikhomirov, Alexander
Abstract: This study was performed to investigate water and gas exchange in the experimental model of a closed ecological system (CES) intended for an estimated portion of a human in the long-duration (several-month) experiment. The diversity of the vegetable conveyor in the system was increased. Human wastes were involved in mass exchange processes, and human respiratory function was periodically connected to the experimental model of a CES. The experimental model of a CES was used to quantify regeneration of the gaseous atmosphere with oxygen and carbon dioxide loops by linking the photosynthesizing compartment with the heterotrophic compartment (soil-like substrate) and by the periodic connection of the human respiratory function. Under the preset light and temperature conditions, atmospheric CO2 concentration in the CES model intended for a portion of a human was maintained at a level that neither limited photosynthetic processes nor was harmful to humans (800–2000 ppm) during the 154-day experiment. At the same time, O2 concentration did not either drop below 20.8% or rise above 22.6%. The amount of the evapotranspiration water collected in the system could satisfy 50% of the daily water requirement of a human (with all the water used and excreted by the human being processed and used to irrigate plants). The evapotranspiration water did not need to be additionally purified before being used by humans. Thus, in the experimental model of the closed ecological system, human oxygen and food requirements (per 0.05 portion of a human) were matched to the function of the heterotrophic compartment and the photosynthesizing activity of the multispecies uneven-aged higher plant community. Highlights: An experimental model of an ecological system with a high degree of closure was created. Along-duration process in the mode of closed mass exchange was implemented. Results of the study are to be used to create closed-loop processes in the CES.